Nigeria’s economic growth: do remittance inflows really matter? - Eigbiremolen, God’stime Osekhebhen; Nnetu, Vivian Ikwuoma (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
Using quarterly data from 1977-2012, this study examines the role of remittance inflows on economic growth in Nigeria. Unlike most previous studies, we address the problem of endogeneity of the remittance variable. The pattern of remittance inflows within the periods under review suggests that the effect of remittance might not be the same across time periods, and a standard empirical test confirms this dynamic. Ignoring this dynamic, a pooled model reveals that remittance inflows have no effect on economic growth. However, when we account for the dynamics and estimate separate models accordingly, allowing for the effect of remittance to vary across sub-periods, we find that the positive effect of remittance inflows was not only marginally bigger when compared to the pooled model, but it also became important for economic growth. Though relevant for growth, it is worth noting that remittance is not yet a major source of economic growth as the effect is still quite marginal
Argumenta Oeconomica, 2015, Nr 2 (35), s. 67-84
Keywords: Dynamics; economic growth; endogeneity; instruments; remittance inflows; 2SLS